Use of rimegepant as an alternative to triptans in migraine treatment - Jaroń, Aleksandra; Jastrzębska, Katarzyna; Witkowska, Maria; Skotnicka, Joanna; Błaszczak, Karolina; Turek, Monika; Wojciechowska, Klara; Borkowski, Adrian; Sawicki, Mateusz (Quality in Sport, 2024)
Introduction and aim of study: Migraine is a chronic neurological disorder that is considered one of the leading causes of disability worldwide. Increasing evidence indicates that the calcitonin gene-related peptide (CGRP), a neuropeptide released during trigeminal nerve activation, plays a major role in pathophysiology and serves as an important therapeutic target. Rimegepant is an antagonist for the receptor of this peptide and an alternative to the commonly used triptans. Materials and Methods: Two databases, Pubmed and Medline, were searched using the terms "rimegepant" and "migraine." Results: By reducing the severity and frequency of migraine attacks, rimegepant significantly improves patients' daily functioning and quality of life. A single 75 mg dose of rimegepant provided better efficacy than placebo in the acute treatment of migraine. Two hours after dosing, significantly more patients in the rimegepant group than in the placebo group reported pain relief (59.3% vs. 43.3%). Rimegepant was also effective in the long term when taken every other day for preventive treatment of migraine and/or as needed for acute migraine treatment. When used, rimegepant was well tolerated in both acute and preventive migraine treatment. The most common adverse events included nasopharyngitis, nausea, urinary tract infection, and upper respiratory tract infection. Conclusions: Rimegepant is an effective drug for treating migraine attacks, offering quick and long-lasting pain relief with a favorable safety profile, especially for patients with contraindications to triptans. Therefore, rimegepant represents a valuable alternative for patients who do not respond adequately to other available migraine therapies.